MAPPING SPATIAL VARIABILITY OF ECOLOGICAL FOOTPRINTS IN OLIVE (OLEA EUROPAEA L.) FRUITS, OIL, AND SOILS THROUGH ELEMENTAL PROFILING - Mahjabeen Tafazzul; Shaista Anjum; Azmat Ali Awan; Ashif Sajjad; Saadullah Khan Laghari; Abdullah Baloch; Zahoor Ahmed Bazai; Khuram Shahzad; Mohammad Arabi Awan; Munib Ahmed Shafique; Sidra Naeem (Journal of Animal and Plant Sciences, 2026)
This study explored how spatial variation in ecological conditions influences the elemental composition of olive (Olea europaea L.) cultivars and their associated soils. Fruits of Leccino, Coratina, Koroneiki, Frantoio, Arbequina, Arbasona, and Suri from Quetta, Loralai, and Khuzdar sites of Balochistan, Pakistan, were collected and analyzed. Twenty-one elements in soil and fruit and six in oil were quantified by CHNS-O and ICP-OES. Soil analysis revealed high Calcium (Ca), Magnesium (Mg), Phosphorus (P), Iron (Fe), Aluminum (Al), Manganese (Mn), Nickel (Ni), Titanium (Ti), and Zirconium (Zr) in Quetta; elevated Carbon (C), Nitrogen (N), Potassium (K), Sodium (Na), and Boron (B) levels in Loralai, and increased Sulfur (S), Copper (Cu), Barium (Ba), Chromium (Cr), Strontium (Sr) and Zinc (Zn) in Khuzdar. In olive fruits, notable findings included high C in Arbequina, Hydrogen (H) in Suri (Loralai), N, Mg, and Ca in Arbequina and Frantoio (Loralai), and K, P and S in Leccino. Olive oil analysis revealed Ca in Arbequina (Quetta), Fe in Coratina (Loralai), K in Leccino (Loralai), Mn in Frantoio (Loralai), and Zn in Koroneiki (Khuzdar). Moderate to high Ca, K, Mg, P, S, Na, B, Mn, Titanium (Ti), and Zn levels in soil may not directly translate to plant uptake, as confirmed by fruit analysis. Essential elements (Ca, K, Mg, P, Cu, Zn, Na, Al, Mn, Fe, Ba, Cr) were within optimal ranges, and non-essential elements Sr and Ti remained within safe limits. Elemental interactions in soil influenced varietal accumulation potential. Among fruits, Arbequina and Suri were notable for elemental accumulation, while Coratina (Loralai) was a mineral-rich oil source with high Ca, Mg, Fe, and Zn. These findings provide baseline data for establishing permissible limits in olives and their products, supporting sustainable agriculture and regulatory guidelines.
Keywords: Balochistan; Elemental composition; Olive cultivars; Olive fruits and oil; Soil